CONCEPÇÕES QUE ORIENTAM ATUAL AGENDA DE EDUCAÇÃO INTEGRAL NO BRASIL: UMA ANÁLISE DE CADERNOS DO “PROGRAMA MAIS EDUCAÇÃO” - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
This paper studies the current unabridged education agenda in Brazil, expressed by the More Education Program - “Programa Mais Educação”. The research goal is to analyze the unabridged education conception presented in this agenda, therefore it was necessary to discover the theorical and practical conceptions in this Program, showing how this conceptions contribute for social maintenance or makeover, as well as understanding the full-time education work nowadays. The problem which leads this analysis was defined as: What are the “Programa Mais Educação” theorical and practical conceptions? This paper tends to be a bibliographic and documentary research and the notebooks which compose the “Mais Educação” trilogy were selected for this analysis because they synthesize the main conceptions from the program. The applied method was the historical and dialectical materialism because it exhibits the contradictions of what is real. The research emphasizes the relation among the unabridged education, the integral attention and the full-time education, based on Rodrigues and Brandalise (1998) and Demo (1994). After that, the hegemonic conception of the unabridged education in Brazil is shown, as from Gallo (2011), D‟Ambrosio (2012), Moll (2012) and Cavaliere (2002). Contradicting the hegemonic viewpoint, the ontological concept of education is handled, aiming for the omnilaterality (which means to develop the most human potentiality), following Marx (2004), Marx and Engels (1999), Tonet (2013), Tonet and Lessa (2011), Saviani (1994), Lukács (2013), Meszáros (2014) and Ferreira Jr and Bittar (2008). It also retracts a historical overview of the main experiences on the unabridged education in Brazil, as well as the place the integral education takes in the educational policy, as from the ideas of Coelho (2005;2009), Rodrigues and Brandalise (1998), Vasconcelos (2012), Saviani (2007), Freitas (2015), among others. The Polity basics are also explored, from de Hobbes (2002), Locke (2006), Rousseau (2006), among others. This way, the unabridged education viability is a problem if it is promoted by an educational institution which doesn‟t represent everyone‟s concerns, as Mascaro (2015), Mészáros (2002), Gruppi (1986), Masson (2010) e Tible (2013) tell. Next, the productive restructure process jn Brazil is studied in every respects, also the neoliberal influence on the proposal for the unabridged education from the 90‟s and the public-private relation on the education, based on authors like Bianchetti (1999), Antunes (2014), Ferreti (1992), Peroni (2006, 2013), Mészáros (2002; 2011). At last, this text deals with the unabridged education agenda in Brazil, which is influenced by two other agendas, the post-modern agenda and the agenda globally structured for the education, and also by the context of the notebooks elaboration, based on Wood (1999), Eagleton (1998), Masson (2009), Dale (2004) e Flach (2005). The results in this research show that the theorical and practical conceptions from the Program are influenced by the international organizations and by the post-modern agenda, keeping away from a really integral education and contributing for the conservation of the current sociability way
Keywords: educação integral; concepções que orientam o “Programa Mais Educação”; capitalismo; emancipação humana; unabridged education; conceptions from “Programa Mais Educação”; capitalism; human emancipation; CNPQ::CIENCIAS HUMANAS::EDUCACAO